초등학생의 따돌림 경험이 따돌림 동조에 미치는 영향: 자아탄력성의 매개효과를 중심으로 - 이현주; 권수정; Lee, Hyun-Ju; Kwon, Soo-Jung (한국콘텐츠학회 논문지, 14(11), 2014)
The purpose of this study is to investigate the mediating effect which may operate within bulling-related experience and bulling conformity types in upper-grade elementary school children. The parameter name is ego-resilience. The participants in this research consisted of 445 upper-grade elementary school children. The main result are the following. First, bulling-related experiences had a direct influence upon bulling conformity types (attacker conformity to the victims. conformity, bystander) without using the parametric ego-resilience. Expecially, the bulling-related experience had a positive relationship with attacker conformity. Second, based on the analysis of the relationship between bulling-related experience and bulling conformity types, using the parametric ego-resilience, it was found out that the bulling-related experience have an effect on bulling conformity types both directly and indirectly. Concretely, the parametric ego-resilience has increased from victim conformity and bystander, but decreased from attacker conformity. 본 연구에서는 초등학생의 따돌림 경험이 따돌림 동조유형에 자아탄력성을 매개로 어떠한 영향을 미치는지 알아보았다. 조사대상자는 경상남도 김해시, 창원시 소재 445명의 초등학생 5, 6학년 대상으로 이루어졌다. 연구방법은 AMOS 18.0과 SPSS 14 프로그램을 이용하여 분석하였다. 연구결과는 다음과 같다. 첫째, 따돌림 경험은 따돌림 동조(가해자 동조, 피해자 동조, 방관자)에 직접적으로 영향을 미치고 있었다. 특히, 따돌림 경험은 따돌림 동조유형 중 가해자 동조와 정적관계에 있었다. 둘째, 자아탄력성을 매개하여 집단따돌림 경험과 따돌림 동조유형간의 관계를 확인해 본 결과, 집단따돌림 경험은 따돌림 동조에 직 간접적 영향을 미치고 있었다. 따돌림 경험은 자아탄력성을 매개하여 가해자 동조를 낮추고, 피해자 동조와 방관자 유형은 증가시키는 것으로 나타났다. 이러한 결과는 학대를 당한 아동이 학대가해자를 동조하고 있고, 자아탄력성의 영향을 통해서 피해자 동조 및 방관자적인 태도를 취하는 것으로 나타났다. 따라서 피학대 아동의 상담 및 치료에서 아동의 자아탄력성 강화와 관련한 접근방법이 요구된다고 하겠다.